Relationship between Serum Sirtuin 1 and Growth Hormone/Insulin-like Growth Factor 1 Concentrations in Children with Growth Hormone Deficiency and Idiopathic Short Stature - Anna Fedorczak; Dorota Kowalik; Justyna Kopciuch; Ewa Głowacka; Katarzyna Mikołajczyk; Marcin Tkaczyk; Andrzej Lewiński; Renata Stawerska (Biomedicines, 2024)
Sirtuin 1 (SIRT1) inhibits growth hormone (GH) intracellular signaling for the insulin-like growth factor 1 (IGF-1) synthesis via the janus kinase (JAK)/signal transducer and activator of transcription proteins (STATs) pathway. The aim of this study was to compare SIRT1 concentrations in children with GH deficiency (GHD) and so-called idiopathic short stature (ISS, non-GH deficient), in order to determine the possible impact of changes in serum SIRT1 concentrations on the GH-IGF-1 axis. The study group included 100 short-stature children: 38 with GHD and 62 with ISS (maxGH in two stimulation tests <10 and ≥10 ng/mL, respectively). The control group consisted of 47 healthy, normal-height children. For each child, the concentrations of SIRT1, IGF-1 and insulin-like growth factor-binding protein 3 (IGFBP-3) were determined and the IGF-1/IGFBP-3 molar ratio was calculated. The level of SIRT1 was significantly higher in both groups of short children than in the controls (p < 0.0001), but there were no differences between GHD and ISS (mean ± SD: 0.89 ± 0.45 for ISS; 1.24 ± 0, 86 for GHD; and 0.29 ± 0.21 for controls). A significant negative correlation was found between SIRT1 and height standard deviation score (SDS), IGF-1 and IGF-1/IGFBP-3, but not between SIRT1 and maxGH. Elevated SIRT1 levels may serve as one of the mechanisms through which the secretion of IGF-1 is reduced in children with short stature; however, further research is required to confirm this issue.